E-INPES MARKETPLACE MEDIA PENGEMBANGAN PROMOSI USAHA PESANTREN DI JAWA BARAT - Fachrul Dena; Fariq Irham Hudiya; Irfan Alfaridzi Ramadhan; Dwi Retno; Amir Machmud; Adam Hermawan (Universitas Pendidikan Indonesia, 2022)
This study aims to develop a web-based e-Marketplace system as a promotional media for Islamic boarding schools products. In the development of this system using the waterfall method and using Object Oriented Analysis Design as a method of analysis and system design, while for the analysis of costs and benefits using the payback period and Return on Investment (ROI) methods. The result of this research is a web-based e-Marketplace system. The results of the tests carried out on the features contained in the e-Marketplace that have been made run 100% on several popular web browsers. While the test results using the User Acceptance Test related to the level of user acceptance and system features are 100%. Based on the results of system testing that has been carried out, it can be concluded that the e-Marketplace system that was created can run well and the level of acceptance of the system is also very good, so the system can make it easier for MSME actors to promote their products widely